Life cycle impact assessment of safety shoes toe caps realized with reclaimed composite materials. (1st May 2022) - Bianchi, I.; Forcellese, A.; Simoncini, M.; Vita, A.; Castorani, V.; Arganese, M.; De Luca, C.
Abstract: Toe cap for safety shoes is an extremely important protective equipment to prevent injuries caused by falling objects. It can be considered that more than 600 millions toe caps are disposed every year, without the possibility of disassembly them from the shoes. This represents a serious concern and sustainable solutions must be found to decrease the weight on the environment generated by the safety shoe market. In this context, a valid answer can be found in the use of carbon fiber prepreg scraps that can be employed in a circular economy approach, avoiding their disposal in landfill or through incineration, to produce certified and light toe caps. Unfortunately, carbon fiber scraps are associated to high production cost and environmental impacts (mainly due to the high energy requirement for the manufacturing of carbon fiber). Thus, the development of a zero-waste system is mandatory to achieve a conscious use of the resources. In this paper, a reclaim method for prepreg scraps and the relative manufacturing process for toe caps are assessed from the environmental point of view. The impacts are compared with those of a traditional process based on a thermoplastic material (Polycarbonate). Results demonstrate that the reclaim process is extremely sustainable due to the low energy requirements. However, some improvements of the manufacturing process are necessary to make toe caps realized with prepreg scraps more sustainable than the traditional ones. Graphical abstract: Image 1 Highlights: Environmental comparison between two different manufacturing methods for safety shoe toe caps. Evaluation of a reclaim process for carbon fiber composite prepreg scraps. The reclaim process for prepreg scraps is more sustainable than other recycling methods for composites. The traditional process for manufacturing toe caps is more sustainable than the innovative reclaim method in the evaluated case study. However, to make the latter more sustainable, it is necessary to increase the service life of the molds.